(untitled) (Scientific journal of the Fergana State University, 2023)
The effectiveness of the process of physical education in modern conditions depends on the correct use of means and methods of complex training of physical qualities. There are opinions about the need to organize a stratified approach to the development of physical qualities in schoolchildren, since the implementation of almost all types of exercises requires a comprehensive development and manifestation of all physical qualities. According to A. A. Gudzhalovsky, primary school age is the most favorable period for the development of physical qualities. The study of the above-described issues related to the improvement of the educational process in the physical education of students is very relevant. In order to improve the efficiency of physical training of high school students, it is necessary to increase the volume of compulsory physical education classes up to 10 hours a week, to conduct physical culture-oriented physical education classes aimed at increasing students’ motor fitness. throughout the entire period of study, as well as to install simulators for the development of certain motor qualities during practical classes, such as improving the base, regular scientific and practical seminars with students, which contribute to increasing the level of theoretical knowledge in practical physical training by inviting leading experts in this areas, to introduce innovative pedagogical technologies more widely in the process of physical education, taking into account modern scientific recommendations.